(untitled) (Research, Society and Development, 2022)
It is known that the exploration of natural environments by traditional peoples provides subsidies for management strategies and, therefore, the rescue of traditional knowledge about the use of plants is of great importance. In this context, ethnobotany assumes a fundamental role. In Brazil, ethnobotanical information has subsisted from father to son, through oral transmission, and can be obtained at fairs, through herbalists, and medicinal plant traders. However, this practice declines as urbanization and technology advance beyond large cities. With the aim of rescuing this empirical knowledge and valuing traditional knowledge free dialogue interviews were carried out, with a traditional herbalist of Cuiabá-MT. The interviews took place at the fairs where the herbalist maintains his tents and recorded their knowledge and experiences, as well as their relationship with plants. Of the total number of species sold in its stall, 71.5% are native species, value that reinforces the need for projects and policies aimed at the preservation of native flora, and the economic development of human populations that depend on these resources. The herbalist was concerned about the increasing environmental degradation and the lack of bond between parents and children, which jeopardizes the oral transmission necessary for the maintenance of local knowledge. This study confirms that herbalists are holders of traditional knowledge, and not only carry information about plants, but also about ecology and environmental sustainability.